"I Saw a Different Life. I Can't Stop Seeing It": Perfectionist Visions in Revolutionary Road. Issue 3 (October 2021) - Deb, Paul
Abstract : In this article, I claim that Sam Mendes' Revolutionary Road (2008) is a recent version of the film genre that Stanley Cavell calls the "melodrama of the unknown woman". Accordingly, my discussion focuses on two key elements of that identification: the film's overriding dramatic and thematic emphasis on conversation, and the central characters' relation to the wider social and political concerns of America.